Biochemical Characterization and Synthetic Application of WciN and Its Mutants From Streptococcus pneumoniae Serotype 6B - Gong, Wei; Liang, Min; Zhao, Jielin; Wang, Hong; Chen, Zonggang; Wang, Fengshan; Gu, Guofeng (Frontiers in Chemistry, 2022)
The biochemical properties of α-1,3-galactosyltransferase WciN from Streptococcus pneumonia serotype 6B were systemically characterized with the chemically synthesized Glcα-PP-(CH2)11-OPh as an acceptor substrate. The in vitro site-directed mutation of D38 and A150 residues of WciN was further investigated, and the enzymatic activities of those WciN mutants revealed that A150 residue was the pivotal residue responsible for nucleotide donor recognition and the single site mutation could completely cause pneumococcus serotype switch. Using WciNA150P and WciNA150D mutants as useful tool enzymes, the disaccharides Galα1,3Glcα-PP-(CH2)11-OPh and Glcα1,3Glcα-PP-(CH2)11-OPh were successfully prepared in multi-milligram scale in high yields.